Social capital and cigarette smoking among Latinos in the United States - Li, Shijian (Dove Medical Press, 2012)
This paper presents the results of analyses conducted to examine if social capital indicators were associated with current cigarette smoking and with quitting smoking among a national representative sample of Latinos living in the United States. Data are from 2540 Mexican Americans, Puerto Ricans, Cuban Americans, and Other Latinos who participated in the National Latino and Asian American Survey. A significant inverse association between neighborhood cohesion and current smoking, and a positive association with quitting smoking, were found only among Mexican Americans. No other significant associations were found except for family conflict being associated with higher odds of current smoking with Cuban Americans. Implications of these findings are discussed to unravel the differences in social capital and smoking behaviors among Latino populations.